PREDIABETES RISK FACTOR CONTROL EDUCATION AT THE MUGI ELDERLY POSYANDU IS HEALTHY, DUKUHWALUH VILLAGE - Nabila, Nurun; Adiratna Sekar Siwi; Febi Septiani (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Diabetes Mellitus (DM) is a condition when the body is unable to produce or use insulin effectively, resulting in increased glucose levels in the blood. Before the onset of type 2 DM, it is important to pay attention to the condition of prediabetes. As one of the global health problems, DM can be prevented through proper education and regular monitoring of fasting blood sugar levels. This service aims to identify fasting blood sugar and evaluate the effectiveness of education in increasing knowledge in the elderly. The method used is health education through lectures and interactive discussions at the Mugi Sehat Elderly Posyandu, Dukuhwaluh Village. The results of the activity showed that some of the results of the fasting blood sugar test were within the normal limit. The provision of education was proven to increase the level of understanding of respondents, which was shown by an increase in knowledge scores from the average pre-test of 70.31 to 86.93 in the post-test after the intervention. In conclusion, health education plays an important role in increasing the awareness of the elderly about controlling prediabetes risk factors to prevent the development of diabetes.